Plato, Bioethics’ Master? - Pascual, Fernando (Medicina e Morale, 2000)
Can Plato, who gave though to many basic anthropologic problem, be a point of reference for judging arguments in the field of bioethics? This essay tries to give an answer. The first part presents Plato's global cosmovision. This serves as a setting for this concept of medicine, of health and of medical practice, which forma the second part. A third part presents his ideas about abortion, euthanasia and eugenics. The aim is to offer a precise judgement of what Plato says in order to explain some contemporary issues in bioethics. The following results are obtained: two basic limits in his assertions are individualism and utilitarianism. They both lead to acceptance of euthanasia - in the case of infants; abortion for demographic control and abandonment to their fate of incurables. Some texts would seem to imply that Plato would not have upheld "active" euthanasia of elders and terminally ill persons nor the elimination of the mentally ill. Plato does not affirm a correct relationship between medical doctor and patients. He does, however, leave an opening for the physician's work of persuasion (wise man) vis-à-vis his patients (in need of therapy and dependent on medical intervention). The reason of suffering is only discovered through Christian faith. Its value for personal growth and for the good of the social body is likewise enlightened. Only in this way could that ancient world tendency towards eugenics, abortion and euthanasia be overcome. They are precisely recurring today, due to the loss of those values that Western civilisation had once accepted thanks to Christianity.